Analisis Kadar Sianida Pada Rebung Berdasarkan Volume Ukuran Dari Kecamatan Bajeng Kabupaten Gowa - Arisanti, Dewi; Rasyid, Nur Qadri; Nasir, Muh. (Indonesian Journal of Chemical Research, 2018)
Bamboo shoots are young shoots from bamboo Terubus. Bamboo shoots contain cyanide if consumed can cause shortness of breath, decreased blood pressure, rapid pulse, headache, nausea, diarrhea, mental disorders and seizures. Continuous consumption with low doses causes mumps and dwarfism and neurological diseases. This study aims to determine how much cyanide levels in bamboo shoots and this type of research is a descriptive laboratory experiment. The sample used in this study were 3 samples based on the size of the volume. The sampling technique is by means of purposive sampling that is looking at the criteria based on large, medium and small size types. Analysis of cyanide levels was obtained by UV-Vis Spectrophotometer with a wavelength of 582 nm. The results showed that large size bamboo shoots were height = 27 cm; diameter = 16 cm has a cyanide content of 21.84 mg/kg, medium size were height = 18 cm; diameter = 7 cm has a cyanide content of 18.40 mg / kg and a small size of height = 8 cm; diameter = 4 cm has cyanide content of 4.65 mg/kg. Thus it can be concluded that the greater the size of bamboo shoots have height level of cyanide.